2019
DOI: 10.1021/jacs.8b12142
|View full text |Cite
|
Sign up to set email alerts
|

Oxalic Diamides and tert-Butoxide: Two Types of Ligands Enabling Practical Access to Alkyl Aryl Ethers via Cu-Catalyzed Coupling Reaction

Abstract: A robust and practical protocol for preparing alkyl aryl ethers has been developed, which relies on using two types of ligands to promote Cu-catalyzed alkoxylation of (hetero)­aryl halides. The reaction scope is very general for a variety of coupling partners, particularly for challenging secondary alcohols and (hetero)­aryl chlorides. In case of coupling with aryl chlorides and bromides, two oxalic diamides serve as the powerful ligands. The tert-butoxide is first demonstrated as a ligand for Cu-catalyzed cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 83 publications
(40 reference statements)
0
86
0
Order By: Relevance
“…More importantly, the challenging electron‐neutral aryl chlorides also worked well, albeit at a higher catalytic loading (15 mol %; 7 – 9 ). However, this was achieved at a lower reaction temperature compared to the thermal reaction catalyzed by copper and nickel systems. Unfortunately, electron‐rich aryl chlorides such as 4‐chloroanisole were found inactive under the current conditions.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…More importantly, the challenging electron‐neutral aryl chlorides also worked well, albeit at a higher catalytic loading (15 mol %; 7 – 9 ). However, this was achieved at a lower reaction temperature compared to the thermal reaction catalyzed by copper and nickel systems. Unfortunately, electron‐rich aryl chlorides such as 4‐chloroanisole were found inactive under the current conditions.…”
Section: Methodsmentioning
confidence: 98%
“…It is noted that functionalities such as ester and cyano groups may not be compatible with the conventional strongly‐basic conditions. Indeed, owing to the use of strong bases, transesterification in copper catalysis and the formation of impurities in palladium catalysis due to the cyano group have been reported. In contrast, all tested ester‐ and cyano‐containing electrophiles were suitable for this new method, thus demonstrating the advantage of using organic amines as base.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Pd‐catalyzed methods have dominated in this area due to the milder conditions which ultimately translate to greater toleration of functional groups . Current advances in the Cu‐catalyzed methodology has enabled milder conditions to be realized that are more competitive with Pd‐based methods . Early reports of BippyPhos demonstrated the viability of coupling primary alcohols with aryl halides .…”
Section: Discovery and Development Of Bippyphosmentioning
confidence: 99%
“…During the past few years, Ma and co-workers have reported that the oxalic diamide ligands are powerful ligands for the copper-catalyzed couplings [19,20,21]. In the presence of ligands, the reaction temperature and catalyst loading could be significantly decreased while the yields were increased [22,23,24]. Following these studies, a number of bidentate ligands were reported for the synthesis of N -arylated compounds.…”
Section: Introductionmentioning
confidence: 99%